Entre compromissos e obrigações: um estudo das experiências morais das classes médias e populares no Nordeste na perspectiva da nova sociologia da moralidade - Freitas, Carlos Eduardo (2018)
In the last decade there has been a renewed interest in Brazilian public opinion on the subject of values in society. Similarly, in the social sciences the number of scientific publications dealing with the subject has also grown more directly. In contemporary Brazilian sociology, for example, we have already found some ethnographies available on the moral experiences of individuals, with a greater emphasis on experiences of disrespect and moral relegation, and also on discursive conflicts in everyday interpersonal interactions. However, in addition to the fact that most of the sociological production on values relies mainly on ethnographies carried out in the South and Southeast regions of the country, there are still few sociological researches concerned with mapping the most frequent values and moral variations in the everyday life of social classes. In order to deepen theoretically the sociological knowledge about the relationship between values, identity and agency, this study is based on the theoretical contributions of the new sociology of morality and seeks to empirically investigate the ways in which the actors of the middle and popular classes of the Northeast build and mean their life narratives and social practices based on different notions of good life and justice incorporated and triggered along biographical trajectories.